Fundamentals of educational research and data analysis a Pafte textbook development project - Padua, Robert N.; Santos, Rosita G. (Quezon City Katha Pub., 1998)
Purpose: A book that "attempts to show the strong connection between research and statistics. It deals with model building rather than computations. Useful either as a textbook or a reference material for experts in the field."
Contents: Educational research. Method of research. Data collection. Analysis. Statistical models. Preparation of research reports.
Keywords: Operational Research--Philippines--Handbooks, manuals, etc